2021
DOI: 10.1080/00071668.2020.1868406
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between starch source and gelatinisation degree on performance and small intestinal digestion in broiler chickens

Abstract: 1. A 2 × 2 factorial arrangement was used to test the hypothesis that, in pelleted diets, legume starch is digested less rapidly and to a lesser extent than cereal starch, and that increased gelatinisation through extrusion would eliminate the differences between the starch sources. In addition, the trial examined whether a lower ratio of starch to nitrogen disappearance rate (SNDR) could improve feed conversion ratio (FCR). 2. At 17 d of age, male broilers were randomly distributed among four dietary treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Many studies have shown that different sources of starch affect the growth performance of animals (Del Alamo et al, 2009;Itani et al, 2021). It has been suggested that feeding SDS may improve FCR of birds.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that different sources of starch affect the growth performance of animals (Del Alamo et al, 2009;Itani et al, 2021). It has been suggested that feeding SDS may improve FCR of birds.…”
Section: Discussionmentioning
confidence: 99%
“…The FBP was obtained following air classification of pinmilled dehulled faba beans (white flowering, low-tannin variety) as described by Itani et al (2020). The SBM was ground to pass through a 1 mm sieve in a hammer mill (Münch-Edelstahl, Wuppertal, Germany licenced by Bliss, USA, 18.5 kW, 3000 RPM) before being mixed with other ingredients.…”
Section: Processing Of Main Ingredients and Experimental Dietsmentioning
confidence: 99%
“…Diets were formulated to be isonitrogenous and isoenergetic and to meet or exceed Ross 308 strain average recommendations (Aviagen 2019) for the starter and grower periods for major nutrients (Tables 3 and Tables 4). The SBM-based diet has been presented elsewhere (Itani et al 2020) as part of another experiment.…”
Section: Processing Of Main Ingredients and Experimental Dietsmentioning
confidence: 99%
See 2 more Smart Citations